Identificación de la flora herbácea existente en el Parque Nacional cotopaxi, después de los incendios generados en el año 2014, provincia de Cotopaxi, periodo 2015 - Chisag Aguagallo, Patricio Santiago (2015)
To identify the flora herbaceous existing in the Cotopaxi National Park, after the fire generated in 2014, to prepare a proposal for recovery (reforestation), it was the main objective of the research work, carried out between January and June 2015, by a field trip it was found the presence consumed by the fire generated by forest fires areas, leaving the naked floor view of black color, with the application of the direct method view proceeded to identify the flora herbaceous existing in the study area, having as a result that the bushes (V-AR) are identified 34 species and 102 species belong to herbaceous. (V-HER) As the objective of this study is the flora herbaceous (V-HER), it was identified in the plot P-CH-CH-006 and P 007 with 15 each, followed by the plot P-CH 002, with 14 species, in the plots P-001 and P-CH CH 003 , 10 species were identified in the plot P-CH 005, with 9 species in the plot P-CH 8 010 species and finally into the P --CH-- 004, P-008 and P-CH-CH-009, 7 species were identified respectively….